Analysis of e-learning problems during covid-19 pandemic - Duha Hardiyanti Awalia; Dadi Setiadi; Kusmiyati Kusmiyati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
The occurrence of the Covid-19 outbreak requires the implementation of distance learning by implementing a learning system such as e-learning. There must be problems during the learning process using e-learning. The purpose of the research is to describe the difficulties of e-learning during the Covid-19 pandemic for class X students at SMAN 1 Keruak. The population in this study was all students in the class of X IPA SMAN 1 Keruak, divided into four courses with 120 people. The sample was taken randomly. The research method used is a descriptive research method with a qualitative approach. The research results in e-learning were carried out in 3 stages, namely learning planning, learning process, and evaluation. Students experienced difficulties in the e-learning learning process during the Covid-19 pandemic regarding the readiness of educational institutions, internet connection, internet packages, inadequate devices, and obstacles to understanding the material. During implementing e-learning, students experienced difficulties with the highest percentage of 78%. Based on these results, it can be stated that students experienced difficulties in the e-learning process during the Covid-19 pandemic regarding facilities and infrastructure.